(untitled) (Fiep Bulletin - online, 2014)
This article aims the discussion about the construction of the sense of elegance and masculinity in the image of the Brazilian soccer from 1940 decade, Heleno de Freitas. For the development of the task, we have chosen four Brazilian sporting authors that depict the trajectory of the icon Heleno de Freitas and from them we have extracted some textual cutting to be analyzed. The current theme is part of the research on "Image" of the "Research Group Lires - LEL of PPGE/UGF" in Rio de Janeiro. This study aims for the intensification of looking over the texts as meaning constructors. The methodology that we used in these analysis were contents analysis (BARDIN, 1977), in order to identify the speeches contained. We believe that the interdisciplinary cross of several knowledge areas is a major contribution for the deep understanding of social phenomena. The understanding of the imaginary through a sporting bibliography led us to the conclusion that the sign of elegance in Heleno de Freitas has been registered through the way the authors qualify him as an elegantly dressed person with a slim body, like a ladies man with polite and elegant behavior. This seems to be an important mark in the icon’s life. The athletic body, the slim silhouette, the carefully prepared clothing, the prepared hairdos e and haircuts and the refined manners were easily turned into seduction skills, showing us a male dominant perfection model based on reason, responsibility and seduction, a spirit that allowed that myth and history got together into the imaginary of the time, in a way to reproduce the traditions of a sporting male world.